ECONOMIC EFFICIENCY OF INNOVATIVE APPROACHES IN THE DEVELOPMENT OF SMALL BUSINESS (Bulletin of Innovative Research, 2026)
This article examines the economic significance of applying innovative approaches in the development of small businesses. The study analyzes the impact of digital technologies, modern management mechanisms, and financial innovations on improving the efficiency, competitiveness, and sustainability of small business entities. Based on the research findings, an authorial conceptual model for innovative small business development is proposed. The results of the study can be used in improving state policies aimed at supporting small businesses and enhancing their role in economic growth.